The Effect Of Transparency, Accountability, Training And Accounting Information Systems On BUMDes Financial Management (All BUMDes In Kuantan Singingi Regency) - Nur aini; Desmiyawati Desmiyawati; Julita Julita (Universitas Islam Bandung, 2023)
BUMDes plays an important role in improving the economy of a village. A good benchmark for a BUMDes can be seen from the structure of good governance, so that to manage well BUMDes, quality of human resources are needed in the implementation of BUMDes management which will make BUMDes easily to achieve the goals of the BUMDes for the welfare of rural communities. This research was conducted with the purpose to testing the effect of accountability, transparency, training and use of accounting information systems on the financial management of BUMDes. Sources of data used in this study are primary data and questionnaires as research measuring tools. The population in this study are all BUMDes located in Kuantan Singingi Regency and the sampling technique used is the proportional stratified random sampling method so that a sample of 69 BUMDes is obtained. The statistical results obtained from this study are that accountability, training and use of accounting information systems affect the financial management of BUMDes,S but transparency has no effect on the financial management of BUMDes.